On the analysis and modelling of the effects of high frequency harmonics on classical synchronous generators - Quadri, Syed Quadir Hussain (2020)
High frequency currents are starting to penetrate in power systems due to the rapidly increasing use of high switching frequency power electronic components. While the presence of these power electronic devices is increasing rapidly, the magnitudes of the high frequency currents generated by them are actually very low. Thus, today, research investigating their effects on the components in the power networks is very limited. In anticipation of this emerging high frequency pollution in the networks, this research focuses on modelling the effects of this phenomenon on the armature windings of classical synchronous generators, which today still represent the major source of power generation across the world. The thesis presents work on developing improved modelling tools for performance characterisation of classical wound field, salient pole synchronous generators considering the emerging high frequency pollution. It first presents a fast and accurate synchronous generator simulation model that considers space harmonics and magnetic saturation by proposing optimised lookup tables for flux linkages that make the model development process more efficient. The model is validated against experimental results and is shown to result in significant benefits and flexibility over the more common FE modelling. The thesis then proposes an improved subdomain modelling technique for accurate high frequency copper loss calculation at frequencies as high as 10kHz for round conductors, which showed a drastic improvement in the accuracy compared to the conventional subdomain model. This technique was validated experimentally and then finally both the validated modelling tools were integrated to present a comprehensive SG model that simulated the overall effects of harmonics on voltage, current, torque and high-frequency copper loss waveforms.